Ethnobotanical survey of medicinal plants in the southern mountain area of Kunyu mountain, China - Wang, Zicheng; Li, Zhe; Xu, Zihan; Liu, Xingjie; Wang, Yinglin; Liu, Ye; Zhang, Minghan; Zhang, Huajuan; Li, Xinyu; Zhou, Jie; Li, Jia; Liu, Qian; et al. (Frontiers in Pharmacology, 2025)
IntroductionThe southern mountainous area of Kunyu Mountain is in the Jiaodong Peninsula of China, which is rich in medicinal plant resources. For a long time, the residents in the Southern Mountain area of Kunyu Mountain have used a variety of plants for pharmacy practice and have accumulated rich knowledge of medicinal plants. Although medicinal plants were widely used, there were no reports on the medicinal plants used by residents in the southern mountainous area of Kunyu Mountain. This study aimed to document the medicinal plants and evaluate the associated traditional knowledge possessed by residents of the southern mountainous area of Kunyu Mountain.MethodsThrough face-to-face interviews with 256 residents, the species, preparation, and use of medicinal plants, and related traditional medicinal knowledge were quantitatively analyzed using the Informant Consensus Factor (FIC) and the Relative Frequency of Citation (RFC).ResultsWe identified 338 species of medicinal plants in this study, belonging to 87 families and 230 genera. Among these, Asteraceae was the dominant family and the whole grass was the most commonly used part for drug preparation, and decoction and oral administration were the most common preparation methods and routes of administration, respectively. In terms of utilization rate, Crataegus pinnatifida var. major (0.2), Crataegus pinnatifida (0.2), Platycodon grandiflorus (0.2), Yulania denudata (0.2), and Zanthoxylum bungeanum (0.2) had higher RFC values, and the five plants above were the most important medicinal plants used by the residents in this area. Besides, compared with China Pharmacopoeia, four new therapeutic uses of three known plants were found. Among the 16 disease categories in the International Classification of Primary Care (ICPC-2), Respiratory system diseases (FIC: 0.8), Digestive system diseases (FIC: 0.8), and General and unspecified system diseases (FIC: 0.8) were the most reported.DiscussionThis study lists the species of medicinal plants on the southern mountainous area of Kunyu Mountain. It records their therapeutic uses, which could provide a reference for further chemical and pharmacological studies on medicinal plants.